ANALYSIS OF PQRST WAVE PATTERNS ON NORMAL HEART USING STUDENT EXPERIMENT OF COBRA4 ELECTROCARDIOGRAPH - Amirudin, Dessy
This study aims to analyze the PQRST wave pattern on the heart including amplitude (A), duration of time (t) and frequency (f) in P wave, Q wave, R wave, S wave, and T wave in sitting and lying position, and determine slope (slope) of the curves of each wave in both positions. The main system used is a set of instrument student electrocardiograph experiments. The study was examined by recording the heart electrical activity carried out after installing the cobra4 software in aset of studentelectrocardiograph experiments for 5 and 10 s in two positions. Each position was recorded in 3 different ways to contact the electrode to the skin (i) direct contact, ie without using a gel and gel sensor, (ii) using gel and (iii) using a gel and gel sensor. The output of this recording is the complex PQRST heart wave pattern displayed on the PC. The output data that has been displayed is then extracted using software Ms.. Excel to get the value of amplitude (A), duration of time (t) and frequency (f) and slope. The conclusion from the results of this study is that sitting or lying position does not affect the results of recording, because the fact is that both sitting and lying positions have experimental data that is not much different. In the subject of normal extremity, the amplitude, the duration of time and the largest frequency in each P wave, Q, R, S, and T in both positions are; amplitude (A): 30.14 mV, 11.00 mV, 441.86 mV, 439.86 mV, 15.50 mV; duration of time (t): 0.11 s, 0.04 s, 0.07 s, 0.27 s; and frequency (f): 92.38 Hz, 92.38 Hz, 79.94 Hz, 79.74 Hz, 82.27 Hz. Whereas in the subject A the extremity of the lead is exchanged for each of the largest P, Q, R, S, and T waves is; amplitude (A): 51.00 mV, 20.40 mV, 454.83 mV, 16.84 mV, 173 mV; duration time (t): 0.10 s, 0.04 s, 0.08 s, 0.05 s, 0.2 s; and frequency (f): 89.83 Hz, 84.22 Hz, 85.34 Hz, 85.42 Hz, 85.30 Hz. The appearance of the PQRST wave pattern on the normal elastic lead for each position produces a normal heart wave, but if the leads are exchanged, the PQRST heart wave pattern at each position is reversed.